Challenges of Islamic Boarding School Organizational Culture in The Millennial Generation and The Digital Era 4.0 - Muhith, Abd.; Dwiyono, Yudo; Munawati, Siti; Mustofa, Ali; Haryanto, Sugeng (Nazhruna: Jurnal Pendidikan Islam, 2023)
This research aims to determine the role of the digitalization era as an intervening variable among the millennial generation toward organizational culture in Islamic boarding schools. To find out this, a research question was created which was answered in a hypothesis or temporary research answer, namely that the millennial generation has a significant influence on the organizational culture of Islamic boarding schools. The second hypothesis is that the digital era has a positive and significant influence on organizational culture and the final hypothesis is that the millennial generation has a positive and significant influence on Islamic boarding school organizational culture through the digital era. This research is quantitative research with a survey method, where data is obtained through questionnaires that have been tested for validity and reliability. The research instrument uses a 1-5 Likert scale. In determining the sample from the population using probability sampling using path diagram analysis whose analysis uses structural equation modeling (SEM). The results of the research show that there is a significant influence between the millennial generation on organizational culture, secondly, the digital era has a positive and significant influence on organizational culture and the main finding in this research is that the digital era variable can mediate the millennial generation on organizational culture with its indicators.